2018
DOI: 10.18632/oncotarget.26263
|View full text |Cite
|
Sign up to set email alerts
|

MiR-192, miR-200c and miR-17 are fibroblast-mediated inhibitors of colorectal cancer invasion

Abstract: Colorectal cancer remains a leading cause of cancer-related death worldwide. A previous transcriptomics based study characterized molecular subgroups of which the stromal subgroup was associated with the worst clinical outcome. Micro-RNAs (miRNAs) are well-known regulators of gene expression and can follow a non-linear repression mechanism. We set up a model combining piecewise linear and linear regression and applied this combined regression model to a comprehensive colon adenocarcinoma dataset. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…The expression of miR-200c has been found to correlate with poor prognosis of colon cancer [6].The miR-200 family comprises 5 members, miR-200a/b/429 and miR-200c/141 [7]. Accumulating evidence suggests that miR-200c, a tumour suppressor, has low expression in colon cancer [8][9][10][11]. MiR-200c inhibitors could enhance the viability and proliferation of colorectal cancer cells (CRC), and low miR-200c expression was related to shortened survival of patients with CRC [8,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR-200c has been found to correlate with poor prognosis of colon cancer [6].The miR-200 family comprises 5 members, miR-200a/b/429 and miR-200c/141 [7]. Accumulating evidence suggests that miR-200c, a tumour suppressor, has low expression in colon cancer [8][9][10][11]. MiR-200c inhibitors could enhance the viability and proliferation of colorectal cancer cells (CRC), and low miR-200c expression was related to shortened survival of patients with CRC [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, Chen J et al [6] reported an opposite conclusion in colon cancer showing that miR-200c was highly expressed in colorectal cancer and functions by inhibiting protein tyrosine phosphatase gene expression and p53 phosphorylation. The regulation of colon cancer metastasis by miR-200c is mediated by a complex biological network [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, inhibition of Fli-1 or TCF12 in CAFs counteracts the contractile activity induced by CAFs, but overexpression of Fli-1 or TCF12 in NFs increases the contractile activity of these NFs. In another study, a combined regression model was used to identify the subgroup-specific miRNAs and functional gene sets in colorectal cancer, and that the results indicated that some miRNAs can regulate ECM target genes [139]. Further studies showed that the high expression of miR-192, miR-17 and miR-200c in fibroblasts can regulate ECM target gene expression at the protein level, thus regulating ECM remodeling.…”
Section: Invasion Migration and Metastasismentioning
confidence: 99%
“…12,13 Abnormal expression of miR-17 is also associated with colorectal cancer, cervical cancer, pancreatic cancer, as well as non-small cell lung cancer. [14][15][16][17][18] Besides, miR-17 may be involved in endometriosis and adenomyosis. 19,20 Long non-coding RNAs (lncRNAs) are important upstream regulators of miRNA regulating physiological process by binding to miRNA.…”
Section: Introductionmentioning
confidence: 99%